The best of Shakespeare - Nesbit, E. (Edith), 1858-1924 (Iona and Peter Opie library of children's literature., 1997)
Simplified prose retellings of Romeo and Juliet, Hamlet, The Merchant of Venice, Othello, The Tempest, King Lear, Macbeth, As You Like It, Twelfth Night, and The Winter's Tale.